Spatial Signature Algorithm (SSA): A New Approach In Countermeasuring XML Signature Wrapping Attack - Madihah Mohd Saudi; Nurzi Juana Mohd Zaizi; Azreena Abu Bakar; Khaled Juma Ahmed Swessi (Scientific.Net, 2024)
Indexed by ERA